The Language of Biosimilars: Clarification, Definitions, and Regulatory Aspects - Declerck, Paul (Drugs, 2017)
Biologic therapies have revolutionized treatment of a number of diseases. Patents and exclusivity for a number of biologics are expiring. This has created the opportunity for the development and approval of biosimilars. Biosimilars are biologic products developed using a step-wise approach to result in a biologic that demonstrates no clinically meaningful differences in terms of quality attributes, efficacy, safety, and immunogenicity compared with an existing licensed, originator biologic. As more biosimilars receive regulatory approval and reach the market, it is increasingly important for healthcare providers to understand the terminology about biosimilars. To help support healthcare providers, the aim of this manuscript is to (i) support understanding of the language of biosimilars, (ii) review the regulatory and manufacturing processes employed in developing a biosimilar, and (iii) provide information for clinical decisions about the use of biosimilars. Because biologics are large, structurally complex proteins, biosimilars cannot be considered generic equivalents to the originator. Biosimilars are developed and evaluated using rigorous processes involving detailed analytical and functional studies, nonclinical assessments, and clinical trials. Clinical studies evaluating the potential biosimilar are designed differently than those for approval of a novel biologic since the aim is merely to confirm similar efficacy and safety and not to demonstrate clinical benefit per se. Extrapolation of data may be used to grant approval of biosimilars in indications not directly evaluated in clinical studies using the biosimilar.